2016
DOI: 10.3906/sag-1410-65
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation profile of GSTP1 and RASSF1A in prostate cancerand benign hyperplasia in Vietnamese men

Abstract: GSTP1 and RASSF1A methylation was accurately detected using the validated MSP method and can be used as a biomarker to diagnose prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…The mRNA expression level of GSTP1, RASSF1, and DNMT3B in PCa patients who responded to hormone therapy was significantly upregulated (p<0.05), HDAC gene expression did not show any significant changes (P=0. 19) and DNMT3A gene expression was significantly decreased after the treatment (P=0.02) ( Figure 1). The qRT-PCR results were used for assessment of the relative expression of the examined genes in two evaluated groups.…”
Section: Expression Variation Of the Examined Genesmentioning
confidence: 94%
See 2 more Smart Citations
“…The mRNA expression level of GSTP1, RASSF1, and DNMT3B in PCa patients who responded to hormone therapy was significantly upregulated (p<0.05), HDAC gene expression did not show any significant changes (P=0. 19) and DNMT3A gene expression was significantly decreased after the treatment (P=0.02) ( Figure 1). The qRT-PCR results were used for assessment of the relative expression of the examined genes in two evaluated groups.…”
Section: Expression Variation Of the Examined Genesmentioning
confidence: 94%
“…17 Therefore, they are among the candidate genes as biomarkers for early detection of prostate cancer in Kashmir, Vietnam, and a large number of other populations. 16,18,19 Inês Graça (2016) stated that potential therapeutic agents for managing prostate cancer are epigenetic changes of the disease which highlights the important role of epigenetic modulators in pre-trial and clinical trials. 20 In addition, it is well understood that HDAC, DNMT3A, and DNMT3B are major epigenetic factors regulating methylation patterns of GSTP1 and RASSF1 genes which alter the expression of the genes in prostate cancer.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…[42] Compared with the traditional detection method, RASSF1A promoter methylation has shown better sensitivity and specificity in the diagnosis of prostate cancer. [43] The meta-analysis investigated the diagnostic value of RASSF1A methylation for prostate cancer and included 20 studies involving a total of 2409 patients. The results show that the pooled sensitivity and specificity were 0.64 and 0.80, with missed diagnosis rates was 0.36 and 0.20, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty studies were published between 2002 and 2018 and included 1640 prostate cancer patients and 769 controls. Eight studies were conducted in Europe, [19][20][21][22][23][24][25][26] six studies were conducted in Asia, [27][28][29][30][31][32] and six studies were conducted in North America. [33][34][35][36][37][38] The quality assessment results of the included studies showed that the included studies had high quality and could be used for meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%